FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN PASIEN RAWAT INAP KELAS III RSUD X - Dini Sukmalara (Jurnal Afiat : Kesehatan dan Anak, 2019)
Introduction satisfied is the level of state that is felt in accordance with patient expectations. RSUD X is a type C hospital inaugurated in 2006. Audit data on satisfaction perceptions in 2015 stated that class III hospitalizations were dissatisfied with nurses' attitudes 40.5%, nursing actions 37.1%, and cleanliness 51.7%. The purpose knowing the factors that influence patient satisfaction in class III inpatients in RSUD X. Research Method Research design is descriptive narrative. The patient population is all inpatients, class III in Hospital X the number of patients an average of 200 patients / month, the population in one week is 50 patients. The sampling technique was purposive sampling with 44 respondents. The results of univariate analysis showed that patients were satisfied with reliability 68.2%, patients were less satisfied with responsiveness 52.3%, patients were satisfied with assurance 61.4%, patients were satisfied with empathy 54.5%), patients were satisfied with tangibles 60.4% . Conclusions show that patients are less satisfied with, nurses do not provide special time to help patients (walking, urinating / defecating) 68.2%, patients are less satisfied nurses do not prepare drugs to be taken 61.4%, nurses do not ask about the patient's appetite 53 , 3%, and the patients are not satisfied The bathroom floor is less clean, slippery and smells 50%. Suggestions to improve patient satisfaction, especially responsibility in this case must pay attention to personal hygien and drug administration of patients.